Frequent and increased expression of human METCAM/MUC18 in cancer tissues and metastatic lesions is associated with the clinical progression of human ovarian carcinoma - Guang-Jer Wu; Erin B. Dickerson (Elsevier, 2014)
Objectives: Human METCAM/MUC18 (huMETCAM/MUC18), a cell adhesion molecule, plays an important role in the progression of several epithelial cancers; however, its role in the progression of epithelial ovarian cancers is unknown. To initiate the study we determined expression of this protein in normal and cancerous ovarian tissues, cystadenomas, metastatic lesions, and ovarian cancer cell lines. Materials and methods: Immunoblotting and immunohistochemical (IHC) methods were used to determine huMETCAM/MUC18 expression in lysates of frozen and formalin-fixed, paraffin-embedded tissue sections of normal human ovaries, and ovarian (benign) cystadenomas, carcinomas and metastatic lesions. We also determined expression levels of several downstream effectors of METCAM/MUC18 in these tissues. Results: HuMETCAM/MUC18 levels in ovarian carcinomas and metastatic lesions were significantly higher than in normal tissues and cystadenomas. IHC results showed that expression of huMETCAM/MUC18 in normal tissues and cystadenomas was mostly absent from epithelial cells, but in carcinomas and metastatic lesions it was localized to epithelial cells. In higher pathological grades of ovarian cancer and metastatic lesions, the percentage of cells stained in IHC was increased. Thirty percent of normal tissues weakly expressed the huMETCAM/MUC18 antigen, but 70% of cancer tissues and 100% of metastatic lesions expressed the antigen. Expression levels of several downstream effectors of huMETCAM/MUC18, Bcl2, PCNA and VEGF, were elevated in cancerous tissues, however, not that of Bax. The phospho-AKT/AKT ratio was elevated in metastatic lesions. Conclusion: Upexpression of huMETCAM/MUC18 may be a marker for the malignant potential of ovarian carcinomas. Progression of ovarian cancer may involve increased signaling in anti-apoptosis, proliferation, survival/proliferation pathway, and angiogenesis.